IMPLEMENTASI GAME EDUKASI PENGENALAN BINATANG BUAS PADA ANAK USIA DINI - AMAN, MUSTAR (Insan Pembangunan Sistem Informasi dan Komputer (IPSIKOM), 2021)
ABSTRACT The use of educational game technology in the teaching and learning process of children is one of the right ways, Educational games are games that are packaged to stimulate thinking power and are one way to train the concentration of users. The problem that occurs at the Tangerang Regency Early Childhood Education Institution is that it has not implemented educational games as an alternative to learning and problems in delivering subject matter at an early age, one of which is child boredom in learning and in understanding the learning material provided, because the concept of learning is still conventionally used. includes child-centred early childhood. The learning approach used is a scientific approach (a series of processes of observing, asking, gathering information, reasoning, and communicating, all the senses and various sources and learning media. The purpose of the research is to overcome learning problems in increasing interest in learning, helping the development of intelligence and improving children''s abilities in learning). the learning process of children at an early age. For this reason, interactive, interesting, and fun learning media are needed so that the delivery of this educational game can be done by playing while learning. The research method used is the Multimedia Development Life Cycle method which consists of six stages, namely conceptualization , designing, collecting materials, making, testing, and distributing, but in this study it was limited to the testing stage.The results of the research were in the form of a mobile game application as an alternative medium of learning for Early Childhood Education teachers in changing the way of learning. Conventional games become a way of learning simulation games, so they can develop children''s creativity, because educational games have elements of challenge, accuracy, reasoning and ethics. Keywords: Game, Education, PAUD, Wild Animals. ABSTRAK Penerapan teknologi Game pada proses belajar pada anak usia dini merupakan cara yang tepat, Game edukasi merupakan permainan yang dikemas untuk merangsang daya pikir dan termasuk cara untuk melatih meningkatkan konsentrasi anal usia dini. Masalah yang terjadi pada Anak Usia Dini Kabupaten Tangerang adalah belum menerapkan game edukasi sebagai alternative pembelajaran dan masalah dalam penyampaian materi pelajaran pada anak usia dini salah satunya seperti kebosanan anak dalam belajar serta dalam memahami materi pembelajaran yang diberikan, karena konsep pembelajaran masih secara konvensional. Pendekatan pembelajaran yang digunakan pendekatan saintifik (rangkaian proses mengamati, bertanya, mengumpulan informasi, menalar, dan mengkomunikasikan, seluruh indera dan berbagai sumber dan media pembelajaran. Tujuan penelitian adalah untuk meningkatkan minat belajar, membantu perkembangan kecerdasan dan meningkatkan kemampuan anak dalam peroses belajar anal usia dini. Untuk itu diperlukan media pembelajaran yang interaktif, menarik, dan menyenangkan sehingga penyampaian Game edukasi ini dapat dilakukan dengan bermain sambil belajar. Metode penelitian yang digunakan adalah metode Multimedia Development Life Cycle yang terdiri dari enam tahap yaitu pengonsepan, pendesainan, pengumpulan materi, pembuatan, pengujian, dan pendistribusian, namun dalam penelitian ini dibatasi sampai tahap pengujian saja. Hasil penelitian berupa aplikasi mobile game sebagai media alternatif pembelajaran guru Pendidikan Anak Usia Dini dalam mengubah cara belajar konvensional menjadi cara belajar simulasi game, sehingga dapat mengembangkan kreativitas anak, karena dalam game edukasi memiliki unsur tantangan, ketepatan, daya nalar dan etika. Kata Kunci: Game, Edukasi, PAUD, Binatang Buas.